Social information affects prospecting, but not settlement, by Black‐and‐white Warblers (Mniotilta varia). (3rd February 2021) - Mann, Justin T.; Mann, Evan A.; Clark, Anne B.
Abstract : Birds use social as well as environmental cues to inform their habitat selection decisions. By manipulating social cues with song playbacks, biologists can influence where individuals search for breeding territories, which could be useful for conservation. Yet before we can predict how birds will respond to playback treatments, we must first understand how they integrate social cues with information about habitat quality at different stages in the habitat selection process. In this experiment, we examined whether vegetation structure and/or social cues affected Black‐and‐white Warbler Mniotilta varia abundance at three study areas that differed in habitat quality. We monitored Black‐and‐white Warbler habitat use across the breeding season, from the early prospecting period until after settlement decisions were made. During seasons without playback treatments, Black‐and‐white Warbler abundance was positively associated with levels of understorey vegetation cover. We then played Black‐and‐white Warbler songs daily for 5–6 weeks at selected survey sites at all study areas. We found that the model‐predicted abundance of Black‐and‐white Warblers was nearly three times greater at playback sites than at control sites during the prospecting period. During seasons with playbacks, understorey vegetation cover was no longer associated with Black‐and‐white Warbler abundance, indicating that individuals prioritized social information when searching for breeding territories. However, during the post‐settlement period, neither playbacks nor levels of understorey vegetation cover were associated with increased abundance, suggesting that playback treatments did not influence final breeding territory choice. We also found no difference in abundance between playback and control sites at a study area that represented low‐quality habitat, which suggests that playbacks should not induce maladaptive site selection.